Bovine and soybean milk bioactive compounds: Effects on inflammatory response of human intestinal Caco-2 cells. (1st November 2016) - Calvello, Rosa; Aresta, Antonella; Trapani, Adriana; Zambonin, Carlo; Cianciulli, Antonia; Salvatore, Rosaria; Clodoveo, Maria Lisa; Corbo, Filomena; Franchini, Carlo; Panaro, Maria Antonietta
Highlights: Milks and bioactive compounds tested are able to reduce LPS-induced inflammatory responses. B and SB milk bioactive compounds significantly inhibited the expression of (iNOS) mRNA. B and SB milk bioactive compounds significantly inhibited protein expression. The inhibition is dose-dependent. Bioactive compounds were absorbed, metabolized and released by Caco-2 cells in culture media. Abstract: In this study the effects of commercial bovine and soybean milks and their bioactive compounds, namely genistein, daidzein and equol, on the inflammatory responses induced by lipopolysaccharide (LPS) treatment of human intestinal Caco-2 cells were examined, in terms of nitric oxide (NO) release and inducible nitric oxide synthetase (iNOS) expression. Both milks and their bioactive compounds significantly inhibited, dose-dependently, the expression of iNOS mRNA and protein, resulting in a decreased NO production. The NF-κB activation in LPS-stimulated intestinal cells was also examined. In all cases we observed that cell pre-treatment before LPS activation inhibited the IkB phosphorylation. Accordingly, quantification of bioactive compounds by solid phase microextraction coupled with liquid chromatography has shown that they were absorbed, metabolized and released by Caco-2 cells in culture media. In conclusion, we demonstrated that milks and compounds tested are able to reduce LPS-induced inflammatory responses from intestinal cells, interfering with NF-kB dependent molecular mechanisms.